Intranasal administration enhances size-dependent pulmonary phagocytic uptake of poly(lactic-co-glycolic acid) nanoparticles - Seung Ho Baek; Eun-Ha Hwang; Gyeung Haeng Hur; Green Kim; You Jung An; Jae-Hak Park; Jung Joo Hong (SpringerOpen, 2024)
Abstract Background Nanoparticles exhibit distinct behaviours within the body, depending on their physicochemical properties and administration routes. However, in vivo behaviour of poly(lactic-co-glycolic acid) (PLGA) nanoparticles, especially when administered nasally, remains unexplored; furthermore, there is a lack of comparative analysis of uptake efficiency among different administration routes. Therefore, here, we aimed to comprehensively investigate the real-time in vivo behaviour of PLGA nanoparticles across various administration routes. PLGA-NH2 nanoparticles of three sizes were synthesised using an oil-in-water single-emulsion method. We assessed their uptake by murine macrophage RAW264.7 cells using fluorescence microscopy. To enable real-time tracking, we conjugated p-SCN-Bn-deferoxamine to PLGA-NH2 nanoparticles and further radiolabelled them with 89Zr-oxalate before administration to mice via different routes. Nanoparticle internalisation by lung immune cells was monitored using fluorescence-activated cell sorting analysis. Results The nanoparticle sizes were 294 ± 2.1 (small), 522.5 ± 5.58 (intermediate), and 850 ± 18.52 nm (large). Fluorescent labelling did not significantly alter the nanoparticle size and charge. The level of uptake of small and large nanoparticles by RAW264.7 cells was similar, with phagocytosis inhibition primarily reducing the internalisation of large particles. Positron emission tomography revealed that intranasal delivery resulted in the highest and most targeted pulmonary uptake, whereas intravenous administration led to accumulation mainly in the liver and spleen. Nasal delivery of large nanoparticles resulted in enhanced uptake by myeloid immune cells relative to lymphoid cells, whereas dendritic cell uptake initially peaked but declined over time. Conclusions Our study provides valuable insights into advancing nanomedicine and drug delivery, with the potential for expanding the clinical applications of nanoparticles.